Recovery after unilateral knee replacement due to severe osteoarthritis and progression in the contralateral knee: a randomised clinical trial comparing daily 2000 IU versus 800 IU vitamin D. Issue 2 (9th July 2018) - Bischoff-Ferrari, Heike A; Orav, E John; Egli, Andreas; Dawson-Hughes, Bess; Fischer, Karina; Staehelin, Hannes B; Rizzoli, Rene; Hodler, Juerg; von Eckardstein, Arnold; Freystaetter, Gregor; Meyer, Ursina; Guggi, Thomas; et al.
Abstract : Objective: To test whether daily high-dose vitamin D improves recovery after unilateral total knee replacement. Methods: Data come from a 24-month randomised, double-blind clinical trial. Adults aged 60 and older undergoing unilateral joint replacement due to severe knee osteoarthritis were 6–8 weeks after surgery randomly assigned to receive daily high-dose (2000 IU) or standard-dose (800 IU) vitamin D3 . The primary endpoints were symptoms (Western Ontario and McMaster Universities Arthritis Index pain and function scores) assessed at baseline, 6, 12, 18 and 24 months in both knees, and the rate of falls over 24 months. The secondary outcomes were sit-to-stand performance, gait speed, physical activity and radiographic progression in the contralateral knee. Results: We recruited 273 participants, 137 were randomised to receive 2000 IU and 136 were randomised to receive 800 IU vitamin D per day. 2000 IU vitamin D increased 25-hydroxyvitamin D levels to 45.6 ng/mL and 800 IU vitamin D to 37.1 ng/mL at month 24 (p<0.0001). While symptoms improved significantly in the operated knee and remained stable in the contralateral knee over time, none of the primary or secondary endpoints differed by treatment group over time. The rate of falls over 24 months was 1.05 with 2000 IU and 1.07 with 800 IU (p=0.84). 30.5% of participants in the 2000 IU and 31.3% of participants in the 800 IU group had radiographic progression in the contralateral knee over 24 months (p=0.88). Conclusions: Our findings suggest that a 24-month treatment with daily 2000 IU vitamin D did not show greater benefits or harm than a daily standard dose of 800 IU among older adults undergoing unilateral total knee replacement.